Biolubricant Production from Parinari Polyandra and Azadirachta Indica Seed Oils using Trimethylolpropane Polyol. - Bulus, L. N.; Odetoye, T. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Environmental pollution over time has raised challenges that elicit concerns for the nearest future. Synthetic lubricants, especially those obtained from petroleum products, contribute to environmental pollution. Thus, there is a need for the production of environmentally friendly lubricant as an alternative to petroleum-based lubricant currently being used. This work explored the potential of Parinari and Neem oils for the production of biolubricant using double transesterification method. Parinari oil was extracted from parinari seed using Sohxlet extraction method, and neem oil was purchased from Akande market in Ogbomoso, Oyo state, Nigeria. Both oils were pre-analysed for physico-chemical properties based on American Society for Testing and Materials (ASTM) methods. Trimethylolpropane (TMP) was used to increase the lubricating property of the transesterified parinari seed oil. The results showed that, the kinematic viscosity for Parinari based lubricant produced ranged between 12.1 – 67.4 cP at 40 ℃ and 15.5-28.6 cP at 100 ℃, while the kinematic viscosity for Neem-based lubricant produced ranged between 55.7 – 647.3 cP at 40 ℃ and 122.9 – 171.6 cP at 100 ℃. Parinari based lubricant had a viscosity index ranging from 159.7-174.4 and neem-based lubricant ranged from 326-365. Viscosities were all compared against SAE standard. SAE 30, 40 and 50 had kinematic viscosities ranging between 9.3-12.5, 12.5-16.3 and 16.3-21.9 respectively. Furthermore, all the biolubricants showed relatively high viscosity indexes with potentials for application in heavy equipment. NBL showed higher kinematic viscosity with longer transesterification reaction time. NBL gave random outputs for each run for biolubricants produced. Therefore, Parinari and Neem oil-based lubricants are potential lubricants as an alternative to petroleum-based lubricant.